MEMBANTU MENINGKATKAN PENJUALAN PRODUK UMKM MASYARAKAT DI MASA PANDEMI MELALUI BISNIS ONLINE - Kadek Bagus Devana Arta; Luh Gede Kusuma Dewi (Universitas Pendidikan Nasional, 2022)
The target community in the Online-Based Real Work Lecture Program (KKNbD) are UMKM actors who experienced a decline in turnover/income in Cempaga village during the covid-19 pandemic. The problem is that the target community does not yet have adequate skills in optimizing the use of the internet and social media as business media. online and do not have an adequate understanding of the legality of online transactions. The methods used are: observation, training and coaching, and evaluation. The result achieved is that the target community has a very high level of participation in online business design training in the midst of a pandemic and can again increase product sales from the target community. Keywords : Online Business Training; Social Media; E-Commerce